Psychomotor Functioning and Alertness with Guanfacine Extended Release in Subjects with Attention-Deficit/Hyperactivity Disorder - Kollins, Scott H.; López, Frank A.; Vince, Bradley D.; Turnbow, John M.; Farrand, Kimberly; Lyne, Andrew; Wigal, Sharon B.; Roth, Thomas (Journal of child and adolescent psychopharmacology, 2011)
To determine whether treatment with guanfacine extended release (GXR) in subjects with attention-deficit/hyperactivity disorder (ADHD) disrupted psychomotor functioning and alertness, or impacted daytime sleepiness. This was a randomized, double-blind, placebo-controlled, multicenter, phase 2, dose-optimization, noninferiority, laboratory classroom study of GXR (1, 2, and 3 mg/day) in 182 subjects aged 6 to 17 years with ADHD. Psychomotor functioning and alertness were assessed through several measures, including the Choice Reaction Time (CRT) test from the Cambridge Neuropsychological Test Automated Battery. Sedative effects were examined via spontaneously reported adverse events of sedation, somnolence, and hypersomnia as well as fatigue and lethargy, and with two validated subject- and observer-rated sleepiness scales. Standard efficacy measures for ADHD also were included. Cardiovascular and laboratory parameters were assessed. There were no significant differences between the GXR and placebo groups on measures of psychomotor functioning or alertness from the CRT at endpoint (least-square mean difference: 2.5 [95% confidence interval (CI): -22.9, 28.0], p = 0.8 for CRT; 2.5 [95% CI: -21.5, 26.4], p = 0.84 for correct responses; 15.5 [95% CI: -45.1, 14.1], p = 0.30 for movement time; and -8.2 [95% CI: -54.1, 37.6] p = 0.72 for total time). Most sedative adverse events were mild to moderate, occurred during dose titration, decreased with dose maintenance, and resolved during the study period. One subject in the GXR group discontinued due to fatigue and somnolence. GXR was not associated with increased daytime sleepiness. GXR treatment was associated with significant improvement in ADHD symptoms (6.3 [95% CI: 2.7, 9.8], p = 0.001 for ADHD Rating Scale IV total scores at endpoint). At doses that resulted in significant improvement in ADHD symptoms, impairment on cognitive tasks was not observed. Daytime sleepiness did not differ with GXR compared with placebo. Results suggest that the beneficial effects of GXR on ADHD symptoms are independent of sedation.